2022
DOI: 10.3390/foods11121671
|View full text |Cite
|
Sign up to set email alerts
|

Valorizing Coffee Silverskin Based on Its Phytochemicals and Antidiabetic Potential: From Lab to a Pilot Scale

Abstract: This study investigates the possibility of valorizing coffee silverskin through the recovery of its bioactive compounds using a sustainable extraction method that could be industrially applied. For that, aqueous extracts were prepared using ultrasonic-assisted extraction (laboratorial scale) and, for comparison, a scale-up of the process was developed using the Multi-frequency Multimode Modulated technology. A concentration procedure at the pilot scale was also tested. The three types of extracts obtained were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…In comparison with other studies, the amounts found in our silverskin extract were higher than those reported by Panusa et al [ 41 ] for a robusta coffee silverskin aqueous extract (caffeine: 3.75 mg/g; CGA (expressed as 5-CQA equivalents): 1.25 mg/g), but the amounts of 5-CQA were relatively similar to those described by Puga et al [ 26 ], where different aqueous silverskin extracts were also prepared by an ultrasound extraction method. Compared to a previous study in which we characterized silverskin extracts from a mixture of arabica and robusta silverskin (kindly provided by a national coffee company, as their major by-product) [ 28 ], in the present study, the obtained values were higher (32.8 against 27.7 mg/g, for caffeine, and 8.09 versus 4.19 mg/g, for total CGA). This was expected, since we focus our study only on silverskin from robusta coffee, which is known to have higher levels of these secondary metabolites [ 41 , 42 ].…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…In comparison with other studies, the amounts found in our silverskin extract were higher than those reported by Panusa et al [ 41 ] for a robusta coffee silverskin aqueous extract (caffeine: 3.75 mg/g; CGA (expressed as 5-CQA equivalents): 1.25 mg/g), but the amounts of 5-CQA were relatively similar to those described by Puga et al [ 26 ], where different aqueous silverskin extracts were also prepared by an ultrasound extraction method. Compared to a previous study in which we characterized silverskin extracts from a mixture of arabica and robusta silverskin (kindly provided by a national coffee company, as their major by-product) [ 28 ], in the present study, the obtained values were higher (32.8 against 27.7 mg/g, for caffeine, and 8.09 versus 4.19 mg/g, for total CGA). This was expected, since we focus our study only on silverskin from robusta coffee, which is known to have higher levels of these secondary metabolites [ 41 , 42 ].…”
Section: Resultscontrasting
confidence: 84%
“…The primer pair for β-actin was: 5′-AGA GCC TCG CCT TTG CCG AT-3′ (forward) and 5′-CCA TCA CGC CCT GGT GCC T-3′ (reverse). Cycling conditions for human GLUT2, GLUT5, SGLT1, and β-actin amplification were the same as those described by Peixoto et al [ 28 ]. Data were analyzed using LightCycler ® 96 SW 1.1 analysis software (Roche, Mannheim, Germany), and the results were analyzed by the Ct method [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from Caco-2 cells treated with the cherry stem infusion or vehicle for 24 h, and quantitative real-time polymerase chain reaction (qRT-PCR) was carried out as described [28]. The primer pair was 5 ′ -CAG GAC TAT ATT GTG GGC TAA-3 ′ (forward) and 5 ′ -CTG ATG AAA AGTGCC AAG T-3 ′ (reverse) for GLUT2, 5 ′ -ACC GTG TCC ATG TTT CCA TT-3 ′ (forward) and 5 ′ -ATT AAG ATC GCA GGC ACG AT-3 ′ (reverse) for GLUT5, and 5 ′ -TGG CAA TCA CTG CCC TTT A-3 ′ (forward) and 5 ′ -TGC AAG GTG TCC GTG TAA AT-3 ′ (reverse) for SGLT1.…”
Section: Real-time Quantitative Reverse Transcription Pcrmentioning
confidence: 99%
“…Barreto Peixoto et al [ 79 ] investigated the effect of silver skin extract on sugar intake. The extract was prepared with 0.5 g silver skin in 25 mL water or a multiple thereof in the laboratory or pilot scale with some difference in extraction methods.…”
Section: Compositional and Toxicological Data On Coffee Silver Skinmentioning
confidence: 99%